Obligacje samorządowe jako źródło dodatkowych środków finansowych wspomagających absorpcję środków funduszowych przez podsektor finansów samorządowych - Smolny, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The work has introduced financial instruments supporting absorption of European Union funds resources by units of local governments. The author is especially interested both in corporation stocks as income of local government units and in the role of banks in these instruments performance. The author describes possibilities of using these instruments and also analyzes development and structure of non-treasury indebted instruments market in Poland between 1997 and 2005. The author points the importance of bonds as sources of additional financial resources for local government units and tendency of changes in this field. She also tries to find reasons for present state. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 332-342